2021
DOI: 10.1097/mph.0000000000002205
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Therapy of Inotuzumab Ozogamicin and Blinatumomab as a Bridge-to Hematopoietic Stem Cell Transplantation in a Pediatric Patient With Primary Refractory Acute Lymphoblastic Leukemia: A Case Report

Abstract: For relapsed/refractory (r/r) acute lymphocytic leukemia (ALL), there is a clinical question on how to combine blinatumomab and inotuzumab ozogamicin (InO), which are newly emerging immunotherapeutic agents, with conventional treatment. We report the case of an 11-year-old boy with B-cell ALL, who had a failed primary treatment and achieved molecular complete remission treated with a sequence therapy of InO and blinatumomab. Later, hematopoietic stem cell transplantation could be performed without major compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…After receiving blinatumomab treatment for 4 weeks, lineage transformation occurred, and the infant eventually died of the primary disease. Recently, some scholars ( 22 , 23 ) explored blinatumomab combined with other antibodies to achieve complete molecular remission in relapsed/refractory ALL or MPAL. Dual-targeted antibody therapy may be an option for some patients with refractory and relapsed ALL or MPAL; however, many prospective studies still need to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…After receiving blinatumomab treatment for 4 weeks, lineage transformation occurred, and the infant eventually died of the primary disease. Recently, some scholars ( 22 , 23 ) explored blinatumomab combined with other antibodies to achieve complete molecular remission in relapsed/refractory ALL or MPAL. Dual-targeted antibody therapy may be an option for some patients with refractory and relapsed ALL or MPAL; however, many prospective studies still need to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Blinatumomab-bridging HSCT should be initiated promptly to improve patient outcomes after a short course of blinatumomabinduced remission. Uchida et al reported a case in which molecular CR was achieved with localized chronic graft-vs.-host disease in a patient who underwent HSCT on the 22nd day after CR in the bone marrow (42). In another study, Chen et al reported the outcomes of two children who underwent allogeneic HSCT within one month of blinatumomab treatment with no implant failure.…”
Section: Discussionmentioning
confidence: 99%
“…A recent case report describes an 11-year-old child with primary refractory ALL in whom repeated cycles of blinatumomab and InO allowed achievement of molecular remission, serving as bridging therapy to a successful HSCT ( 12 ).…”
Section: Strategies Prior To Hsctmentioning
confidence: 99%